استخدام طريقة الدريل لترقية إتقان المفردات لطلاب الصف الحادى عشر فى المدرسة الثانوية الإسلامية الثبات ماكسر - Muhammad Asrar Idrus; Amri Rahman; Sarah Noviyanti Latuconsina (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2022)
This study aims to determine the planning, process and results of improving Arabic vocabulary mastery in learning Arabic using the drill method. This study applied Classroom Action Research (CAR). The subjects of this study were students of class XI Madrasah Aliyah Ats-Tsabat Makassar with a total of 24 students. The techniques of data collection are test and observation. This study consisted of 2 cycles and each cycle consisted of 2 meetings. The results showed that before conducting the research in the first cycle, a test was given to determine the students' initial abilities and the average score of students only reached 69.1%, and then in the final evaluation of the first cycle the average score of students was 91.8%, and in the second cycle the average score of the students reached 96.6%. These results indicate that students' Arabic vocabulary mastery has increased by using the drill method in learning Arabic.